Os conselhos deliberativos das escolas públicas : democracia ou simulacro? - Moreira, Marilene Fonseca Dias (2017)
The objective of this study is to determine the functioning and the performance of Conselho Deliberativo da Comunidade Escolar (CDCE) of the state system of Cuiabá- MT. Three State Public Schools were selected for this empirical research. It started from the understanding that the school councils are constituted as important spaces to the collective deliberations between the community and the school and, in that way, such councils can contribute with the educational process in a more democratic perspective. This investigation was based in the theoretical formulations of the Dialectical Historical Materialism. Authors such as Libâneo et al. (2003), Gramsci (2000), Kosik (1976), Silva and Torres (2008) and some others, can allow us to comprehend the political, economical, social and cultural relations; uncovering the contradictions, understanding how the appearances hide the essences in relation to the implementation of the current educational legislation and the management in which business logic is hegemonic, even in public institutions. This study situates the democratic management and focuses on the schools councils as one of the main pillars of this model of decentralized educational management. The empirical instruments were made based on the following techniques: 1. Application of questionnaires; 2. Semi-structured interviews for the members of the school council and the principals of the schools; and 3. Observation. To get the results were made some theoretical- empirical analyzes about the collected data with the three techniques that were used. From the data obtained was possible to verify, in the three schools investigated, that the deliberative councils are instances manipulated by hegemonic segments of the schools, and it makes difficult the effectiveness of democracy in the school environment, it may even be considered that they are inoperative, especially because it was appreciated that in the three councils researched, the segment that stops, in fact, the power of decision-making is of that direction of schools. It was found that the segments of students and parents are very absents in the meetings, which denotes a non democratic relation of the collegiate; the councils are maintained much more by mere formality of the requirement of the current educational legislation. It was found also that a democratic management in which all are involved in the performance of CDCEs deliberate, express opinions, know the problems of the school nearly, think together about possible solutions, do not happen in the daily practice of the school investigated. The observation showed that many questions that are presented at the meetings are already define by the management team of the schools, making impossible, in that way, the autonomous participation of the counselors, which gives the collegiate researched, an authoritarian behavior in which a segment is overlapped with others, denying the essential of democracy.